Analysis of Road Damage Handling Priority Based on Pavement Condition (Case Study: National III Road, Kabat – Banyuwangi Segment) - Budhi, Wahyu Satyaning; Utanaka, Ahmad; Chandra, Jimmy (STMIK Widya Cipta Dharma, 2025)
Banyuwangi Regency is a leading tourism area designated as a National Tourism Strategic Area (KSPN), making the availability of adequate road infrastructure essential to support regional mobility and accessibility. However, traffic accidents have increased in recent years, particularly on the Jalan Nasional III segment from Kabat to Banyuwangi. This rise in accidents may indicate a correlation with the condition and performance of the road infrastructure. Therefore, a comprehensive evaluation of this segment is required, focusing on three main aspects, there are riding quality, pavement damage level, and drainage conditions as the basis for determining maintenance priorities. The study was conducted through field surveys, including measurements of Riding Quality, calculation of Total Distress Point (TDP), and assessment of drainage system performance in both directions. The analysis shows that the Kabat–Banyuwangi direction has several segments with low ride comfort (Poor), TDP values indicating light to medium maintenance needs, and some drainage points requiring maintenance. In contrast, the Banyuwangi–Kabat direction shows better and more stable conditions in terms of ride comfort, pavement damage, and drainage performance. These findings suggest that maintenance priorities should focus on the Kabat–Banyuwangi segments experiencing the most significant performance decline. This integrated evaluation approach is expected to provide a comprehensive basis for supporting more effective, efficient, and sustainable road maintenance decision-making.